Self-administered acupressure at the Taichong point reduces blood pressure in hypertensive patients - Yasa, I Dewa Putu Gede Putra; Sukawana, I Wayan; Surasta, I Wayan; Rasdini, I Gusti Ayu Ari (Babali Nursing Research, 2024)
Background: Blood pressure control can be achieved through lifestyle changes, pharmacological therapy, and non-pharmacological therapy. Complementary therapies can be included in hypertension management programs and are self-administered. This study aims to analyze the effect of self-administered acupressure at the Taichong point on blood pressure in hypertensive patients. Method: The research was conducted at Puskesmas II Denpasar Utara using a pre-experimental design with 38 primary hypertensive patients. Blood pressure data were measured five minutes before and after the patients performed self-administered acupressure at the Taichong point between the first and second metatarsals. Acupressure was performed with a stick for 5 seconds, lifted for 1 second, and repeated 30 times. Result: The results showed that all respondents had stage 2 hypertension, with systolic blood pressure (SBP) ranging from 140 to 172 mmHg and diastolic blood pressure (DBP) between 90 and 102 mmHg. After the intervention, all respondents experienced a decrease in SBP and DBP, with an average reduction in SBP of 13.89 ± 5.46 mmHg and a reduction in DBP of 11.05 ± 6.32 mmHg. The analysis results showed a significant effect on blood pressure (p-value: 0.0001). Conclusion: This study concludes that self-administered acupressure at the Taichong point significantly reduces blood pressure in primary hypertensive patients.